CONTRASTIVE ANALYSIS OF PREFIXES IN ENGLISH AND BATAK TOBA LANGUAGE - Afriyanti Pakpahan; Lastri Wahyuni Manurung; Febrika Dwi lestari (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study deals with the a contrastive analysis of prefixes between English and Batak Toba Language. The objectives of this study were to investigate the differences and similarity of prefixes in English and Batak Toba to elaborate the morphological process containing prefixes in both language the descriptive qualitative method was used in this study the data collected were analysis based on analysis model including data, reduction, data display and conclusion the research finding ,showed that the English and Batak Toba Language prefixes are sometimes different and similar in terms of form, distribution, function and meaning . in this case ,those were not totally different or some for each aspect it was also found that English and Batak Toba prefixes have the same morphological process to produce or form a word.